READING POPULAR ISLAMIC LITERATURE: CONTINUITY AND CHANGE IN INDONESIAN LITERATURE - Rokib, Mohammad (Center for Research and Development of Religious Literature and Heritage, 2015)
In the last few years, literature on Islamic themes has become increasingly popular in Indonesia. It is commonly categorized as Islamic literature identified by Islamic texts and symbols on the book cover and its content. The literary works have been popular as reflected in the record sales figures. Previously, some literary works dealing with Islamic themes failed to gain public attention. Interestingly, those works are not mentioned by people as Islamic literature. This paper aims to discuss some questions on why are some literary works on Islamic theme mentioned as Islamic while others are not? Is there Islamic literature within Indonesian literature? What are the differences between Islamic literature and kitab literature (sastra kitab) written by Muslim scholars in the Malay world? By exploring the social context of reader responses toward selected literary works on Islam, this study reveals that the label of Islamic literature is created to confront opposite themes in Indonesian literature. The term Islamic literature remains a problematic and debatable issue related to literature based on Islamic themes in both old and modern Indonesian literature.